High-quality draft genome sequence of Rhizobium mesoamericanum strain STM6155, a Mimosa pudica microsymbiont from New Caledonia. - Klonowska, A.; López-López, A.; Moulin, L.; Ardley, J.; Gollagher, M.; Marinova, Dora; Tian, R.; Huntemann, M.; Reddy, T.; Varghese, N.; Woyke, T.; Markowitz, V.; et al. (2017)
Rhizobium mesoamericanum STM6155 (INSCD?=?ATYY01000000) is an aerobic, motile, Gram-negative, non-spore-forming rod that can exist as a soil saprophyte or as an effective nitrogen fixing microsymbiont of the legume Mimosa pudica L.. STM6155 was isolated in 2009 from a nodule of the trap host M. pudica grown in nickel-rich soil collected near Mont Dore, New Caledonia. R. mesoamericanum STM6155 was selected as part of the DOE Joint Genome Institute 2010 Genomic Encyclopedia for Bacteria and Archaea-Root Nodule Bacteria (GEBA-RNB) genome sequencing project. Here we describe the symbiotic properties of R. mesoamericanum STM6155, together with its genome sequence information and annotation. The 6,927,906 bp high-quality draft genome is arranged into 147 scaffolds of 152 contigs containing 6855 protein-coding genes and 71 RNA-only encoding genes. Strain STM6155 forms an ANI clique (ID 2435) with the sequenced R. mesoamericanum strain STM3625, and the nodulation genes are highly conserved in these strains and the type strain of Rhizobium grahamii CCGE501(T). Within the STM6155 genome, we have identified a chr chromate efflux gene cluster of six genes arranged into two putative operons and we postulate that this cluster is important for the survival of STM6155 in ultramafic soils containing high concentrations of chromate.